2000
DOI: 10.1182/blood.v95.3.952.003k27_952_958
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VEGFR-2 and AC133 by circulating human CD34+ cells identifies a population of functional endothelial precursors

Abstract: Emerging data suggest that a subset of circulating human CD34+ cells have phenotypic features of endothelial cells. Whether these cells are sloughed mature endothelial cells or functional circulating endothelial precursors (CEPs) is not known. Using monoclonal antibodies (MoAbs) to the extracellular domain of the human vascular endothelial receptor-2 (VEGFR-2), we have shown that 1.2 ± 0.3% of CD34+ cells isolated from fetal liver (FL), 2 ± 0.5% from mobilized peripheral blood, and 1.4 ± 0.5% from cord blood w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
837
0
46

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,054 publications
(903 citation statements)
references
References 27 publications
20
837
0
46
Order By: Relevance
“…Our study demonstrated that PDGF significantly enhanced the development of adherent cells and clusters from enriched cord blood CD34 + cells. Some adherent cells were endothelial in nature as revealed by the positive VE-adherin expression and they were probably developed from endothelial cell precursors (Peichev et al, 2000) present in the fresh cord blood in a minute quantity (Nieda et al, 1997). Bone marrow stromal cells and cord endothelial cells have been known to enhance the expansion of SCID repopulation cells and long-term haematopoietic progenitor cells respectively (Ye et al, 1994;Yamaguchi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that PDGF significantly enhanced the development of adherent cells and clusters from enriched cord blood CD34 + cells. Some adherent cells were endothelial in nature as revealed by the positive VE-adherin expression and they were probably developed from endothelial cell precursors (Peichev et al, 2000) present in the fresh cord blood in a minute quantity (Nieda et al, 1997). Bone marrow stromal cells and cord endothelial cells have been known to enhance the expansion of SCID repopulation cells and long-term haematopoietic progenitor cells respectively (Ye et al, 1994;Yamaguchi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, vascular endothelial growth factor receptor-2-positive endothelial progenitors are AC133 epitope-positive and AC133 epitope expression is rapidly downregulated during maturation. 47 Down-regulation of AC133 and AC141 epitope expression was also observed upon differentiation of the colon carcinoma cell line Caco-2. 48 AC133 1 AC141 1 CD34 2 CD45 2 cells isolated by FACS from fresh human fetal brain tissue initiated neurosphere cultures, and the progeny of clonogenic cells could differentiate into both neurons and glial cells.…”
Section: Discussionmentioning
confidence: 97%
“…These cells possess an even broader range of differentiation potential than MSCs (Reyes et al, 2001;Reyes et al, 2002;Jiang et al, 2002a). MAPCs can apparently differentiate not only into all MSC-derived cell types (including skeletal muscle-like cells) but also into CD34 + CD133 + VEGFR-2 + VE-cadherin + cells that have properties of endothelial progenitors (Peichev et al, 2000;Quirici et al, 2001). While MAPCs could not be induced to differentiate into hematopoietic cells in vitro under the conditions employed (but see below), they are capable of differentiating in vitro into nonmesodermal cell types, such as hepatocyte-like cells (Schwartz et al, 2002) and cells having characteristics of midbrain neurons (Jiang et al, 2003).…”
Section: Phenotype and Function Of Tissue-specific Stem Cellsmentioning
confidence: 99%